Characterization analysis of the main character in “rambo 4” movie - Merta, I Nyoman Arya; Jayantini , I Gusti Agung Sri Rwa; Ariyaningsih, Ni Nyoman Deni (Institut Pariwisata dan Bisnis Internasional, 2022)
This article discusses the characterization in Rambo 4 movie entitled “An Analysis of Characterization of the Main Character in Rambo 4 Movie”. There are two objectives of this study; the first one is to identify the characterization of the main character in movie Rambo 4. The second one is to analyze the main character described in movie Rambo 4. Qualitative descriptive method was used in analyzing the data. The data source in this study was the movie and the movie script entitled Rambo 4. The data which had been collected were analyzed based on the theory Kenney (1966) and theory Wellek and Warren (1956). The main character is complex (round) character. The characterization of Jhon Rambo can be described as hard working, care, murderer, brave, religious, smart, and ignorant Jhon Rambo can be described physically with long curly hair, panicked face, angry face, catcher snake, simple life, archer, and impolite.